Development of critical and creative thinking skills to increase competence of PLC programming for electrical engineering education students. (May 2019) - Rusimamto, PW; Nurlaela, L; Sumbawati, MS; Munoto,; Samani, M.
Abstract: PLC learning emphasizes on teaching and learning activities as well as developing the concepts and skills of the students process with various teaching methods that are in accordance with the study materials being taught. PLC learning demands an active role for students, because PLC is a scientific process based on logical thinking based on supporting facts. The low ability of students thinking is caused by PLC learning so far only tends to hone aspects of remembering and understanding. Basically students have critical thinking skills in learning such as questioning skills, hypothesis, classification, observation and interpretation. Problem-based learning model (PBL) is a learning model designed on problem solving process that faced scientifically so that students get important knowledge. Thus expected students are adept at solving problems, have their own learning models and have the skills to participate in the team. Teacher's role as a trainer in problem-based learning is asking about thinking, monitoring learning, probbing (challenging students to think), keeping students engaged, organizing group dynamics, keeping the process going. This critical and creative thinking design aims to make students able to think critically and able to consider everything and be able to act on the decisions that have been considered and creative thinking that aims to learners are able to create ideas, or ideas and able to express the idea to solve a problem.